Technology management department agroindustrial smes Atlantic (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2012)
The business management and the constant search for innovation systematic and intensive use of knowledge are critical determinants for successful businesses, all this technology promoted by the management as motor function and integrating business development strategies. This research aims at developing a methodology for the implementation of technological management processes in small and medium companies (PYMES) in the agribusiness department of the Atlántico, for its development was done, first, a study on the current state of technological management of these companies to identify key variables that influence these processes. This information allowed the construction of the proposed methodological model. The study involved in its implementation with financial support from the Department of Administrative Science, Technology and Innovation (COLCIENCIAS), National research training "Bicentennial generation", young researchers and innovative program 2010.
Keywords: SME; agribusiness; methodology; technology management